Safety evaluation of the food enzyme endo‐polygalacturonase from the genetically modified Trichoderma reesei strain RF6197 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The food enzyme endo‐polygalacturonase ((1–4)‐α‐d‐galacturonan glycanohydrolase; EC 3.2.1.15) is produced with the genetically modified Trichoderma reesei strain RF6197 by AB Enzymes GmbH. The genetic modifications do not give rise to safety concerns. The food enzyme was considered free from viable cells of the production organism and its DNA. It is intended to be used in five food manufacturing processes: fruit and vegetable processing for juice production, fruit and vegetable processing for products other than juices, production of wine and wine vinegar, coffee demucilation and production of plant extracts as flavouring preparations. Since residual amounts of the total organic solids (TOS) are removed during the coffee demucilation and the production of flavouring extracts, dietary exposure was calculated only for the remaining three food processes. It was estimated to be up to 0.156 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1,000 mg TOS/kg bw per day, the highest dose tested, which, when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 6,410. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and matches were found with a number of pollen allergens. The Panel considered that, under the intended conditions of use, the risk of allergic reactions by dietary exposure, particularly in individuals sensitised to pollen cannot be excluded. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.